Prevalência e resistência aos antimicrobianos de Campylobacter isoladas de carcaças de frangos comercializadas no Brasil - Iasbeck, Jocasta Rodrigues (2016)
Campylobacter is the most involved zoonotic agent in human bacterial gastroenterite in developed countries. Besides diarrheal framework, resulting from infection by this microorganism, some serious complications can affect population as sepsis, abortion, meningitis, abscesses and Guillain-Barre syndrome (GBS). This information is significant in public health, and this micro-organism is recognized as an emerging pathogen, widely distributed by poultry. The high incidence of diseases related to this micro-organism in humans in Europe and at United States refers to the broader need for knowledge concerning the importance of this agent as a foodborne pathogen in Brazil. The first chapter presents general considerations and theoretical support for understanding the second chapter. The second chapter aimed to determine the prevalence of Campylobacter in poultry carcasses commercialized in Brazil. We analyzed 246 carcasses, frozen and chilled, representative of brands made in the country by different types of sanitary inspection, qualified to internal trade or export. Isolates of gender were identified as C. jejuni, C. coli or Campylobacter spp. The antimicrobial susceptibility was checked and discussed the potential they represent to public health. The results were used to create profiles and resistance determinants to establish a higher positivity of Campylobacter in analyzed poultry carcasses.